ANÁLISE DO SISTEMA DE TELHADO VERDE NA GESTÃO DE ÁGUAS PLUVIAIS - Mustafa, Willian Felipe; Alvim, Carolina Alves do Nascimento (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The disorderly growth of the urban area of the cities is waterproofing the soil, consequently, raising the superficial flow of rain. Urban drainage systems, if not designed for such high demands, will not be able to drain the entire volume of the incident water, thus causing flood problems. One of the solutions adopted by several cities in the world is the replacement of unused roof areas for green roofs. The water retention capacity of green roofs fluctuates according to the seasons and the climate in which it is installed. This work aims to analyze the quantitative behavior of the green roof in rainfall events in the city of Londrina, comparing it with the concrete waterproofed roof and the ceramic roof. A prototype with 1 m² was built for each system. It were analyzed 7 months of rainfall, where an average efficiency of 65% in the water retention on the green roof was verified, against 17% in the ceramic roof, proving the benefit of the use of the rainwater management system.